The impact of halal certification for MSME business: A systematic literature review (Lighthouse Publishing, 2023)
Indonesia is the country that is home to the most significant number of Muslims anywhere in the globe. As a result, there is a considerable demand for halal food and other goods in Indonesia. As a result, halal certification is crucial for the success of Micro, Small, and Medium-sized Enterprises (MSMEs) in Indonesia to fulfill the requirements of an expanding market. Having a halal certification provides various benefits for micro, small, and medium-sized enterprises (MSMEs), including enhancing consumer confidence in the products and services supplied, growing the market due to the preference of many consumers for halal products, and strengthening corporate competitiveness in the global market. This study aims to investigate the effects of halal certification on small and medium-sized businesses. This research was put together utilizing the systematic literature review (SLR) method, and the access journals Google Scholar and Garuda were used in its construction. A total of over one hundred pieces were considered for usage and reviewed based on the criteria that had been established in advance. Twenty articles were found to satisfy the requirements. According to the findings of this research, halal certification is essential for bolstering micro, small, and medium-sized enterprises (MSMEs) to ensure the continuity of production or operation. According to the findings of this survey, buyers of MSME goods and services give more significant consideration to buying products that have received halal certification. It has also been demonstrated that halal certification can help micro, small, and medium-sized enterprises (MSMEs) increase their turnover or sales.